2013
DOI: 10.1519/jsc.0b013e31828a1ffa
|View full text |Cite
|
Sign up to set email alerts
|

Practical Blood Flow Restriction Training Increases Acute Determinants of Hypertrophy Without Increasing Indices of Muscle Damage

Abstract: Vascular blood flow restriction (BFR) training stimulates muscle hypertrophy by increasing muscle activation and muscle swelling. Previous studies used expensive pneumatic cuffs, which may not be practical for regular use. The aim was to investigate the acute effects of low-intensity practical BFR (LI-pBFR) on muscle activation, muscle swelling, and damage. Twelve trained male participants completed a 30-, 15-, 15-, 15-repetition scheme at 30% of their leg press 1-repetition maximum under control and LI-BFR co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
156
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(170 citation statements)
references
References 35 publications
6
156
1
7
Order By: Relevance
“…While using elastic knee wraps for BFR makes it difficult to apply the restrictive stimulus at an exact pressure, Wilson et al [48] have shown this method is effective when wraps are applied to be snug, but not cause pain. These investigators standardized the restrictive stimulus using a perceived pressure scale from 0-10, with a score of 0 indicating no pressure, and 10 indicating intense pressure with pain [48].…”
Section: Restrictive Pressurementioning
confidence: 99%
See 4 more Smart Citations
“…While using elastic knee wraps for BFR makes it difficult to apply the restrictive stimulus at an exact pressure, Wilson et al [48] have shown this method is effective when wraps are applied to be snug, but not cause pain. These investigators standardized the restrictive stimulus using a perceived pressure scale from 0-10, with a score of 0 indicating no pressure, and 10 indicating intense pressure with pain [48].…”
Section: Restrictive Pressurementioning
confidence: 99%
“…These investigators standardized the restrictive stimulus using a perceived pressure scale from 0-10, with a score of 0 indicating no pressure, and 10 indicating intense pressure with pain [48].…”
Section: Restrictive Pressurementioning
confidence: 99%
See 3 more Smart Citations